Effect of protein levels and Zinc-biocomplex supplementation in concentrate diets on performance of young male goats - I, Supriyati; W, Puastuti; IGM, Budiarsana; I-K, Sutama (Indonesian Journal of Animal and Veterinary Sciences, 2015)
This trial was carried out to investigate effects of protein levels and Zinc biocomplex supplementation in concentrate diets on performances of young male Etawah grade goats. Twenty-four young male goats were divided into four groups and received concentrate diets as follows: R0= 14% crude protein (CP), R1= 18% CP, R2= R0 + 60 ppm Zn and R3= R0 + 120 ppm Zn as Zn biocomplex. Initial live weight was 16.39Â±2.19 kg. Animals were offered King grass ad libitum and 400 g/h/d of concentrates diets for 16 week trial. The experiment was conducted based on a randomized complete design with four treatments and six replications. The concentrate diets had no significant effect on DM, TDN, NDF and ADF daily intakes (P>0.05) but significantly (P>0.05) influenced the CP and Zn daily intakes, ADG and FCR. The average DMI, TDN, NDF and ADF daily intakes for all treatments were 670, 547, 333 and 229 g, respectively. The CP daily intake for R0, R1, R2 and R3 treatments were 76.33, 91.83, 75.83 and 76.67 g, and the Zn daily intakes were 42.83, 45.50, 68.83 and 91.33 mg, respectively. The ADG for R0, R1, R2 and R3 were 71.65, 79.96, 78.17 and 82.74 g with the FCR values were 9.95, 8.50, 8.44 and 8.06, respectively. The in vivo digestibility of DM, NDF and ADF were not significant (P>0.05) but the digestibility of CP and GE were significant (P<0.05). The highest IOFC value occurred at R3 treatment. In conclusion, the improvement of CP levels from 14% to 18% in diets increased the goat performance and the supplementation of 120 ppm Zn as Zn biocomplex in diet containing 14% CP gave better performance and increased the IOFC value compared to animals receiving 18% level of CP in diet of young male goat. Key Words: Goats, Concentrates, Performances, Protein, Zn Biocomplex